Stable emulsion produced from casein and soy polysaccharide compacted complex for protection and oral delivery of curcumin. (October 2017) - Xu, Guangrui; Wang, Chaonan; Yao, Ping
Abstract: Casein and soy soluble polysaccharide formed compacted complex aggregates in pH 3–4.5 aqueous solutions by electrostatic and hydrophobic interactions. The diameters of the complex aggregates were about 133 nm. The oil in water emulsion produced from the complex at pH 4 was stable after 500 days of storage in pH 2–6.8 media at 4 °C due to the compacted complex interfacial film. The curcumin loading efficiency of the emulsion was 99.9% and diameter of the droplets was about 324 nm. Only 3% of the loaded curcumin degraded when the emulsion was stored at 4 °C for 40 days. About 73% of the curcumin was released after 2 h digestion of the emulsion in simulated gastric fluid followed by 2 h digestion in simulated intestinal fluid. The curcumin pharmacokinetics in mice was analyzed after oral administration. The curcumin absorption of the emulsion treatment group was more rapid and effective than the absorption of curcumin/Tween 20 suspension treatment group. The curcumin oral bioavailability of the emulsion group was 11-fold higher than the bioavailability of curcumin/Tween 20 suspension group. This study demonstrated that casein and soy polysaccharide complex emulsion is an applicable system for oral delivery of lipophilic nutrients and drugs. Graphical abstract: Highlights: Casein and soy polysaccharide formed compacted complex aggregates. Emulsion produced from the complex had compacted interfacial film. Curcumin-loaded emulsion had very good physical and chemical stabilities. The emulsion was digestible in simulated digestive juices. The emulsion greatly increased curcumin oral bioavailability.